Shanghai Modern: Replaying Futures Past - O´Connor, Justin (Culture Unbound, 2011)
This article discusses different accounts of Shanghai Modern, the period between 1920s and 1940s in which the city occupied a unique position within China and the world. It places discussions of this period in the context of the resurgence of urban led modernization in China, led by Shanghai. It looks in particular at Leo Ou-Fan Lee’s attempt to link the cosmopolitanism of Shanghai modern with prospects for this new post-reform China. I then discuss Ackbas Abbas’ response to this book and use this as a way of reflecting on the progress of Shanghai urban development and its divergence/ convergence with similar processes in the West. The article then looks at the other significant moment of the Cultural Revolution as a way of opening up discussions of Chinese and Shanghainese modernity beyond that of simply an absorption into Western capitalist modernity. It concludes by briefly introducing this volume.